2022
DOI: 10.3389/fpls.2022.1031679
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, comprehensive characterization of transcription factors, cis-regulatory elements, protein homology, and protein interaction network of DREB gene family in Solanum lycopersicum

Abstract: Tomato is a drought-sensitive crop which has high susceptibility to adverse climatic changes. Dehydration-responsive element-binding (DREB) are significant plant transcription factors that have a vital role in regulating plant abiotic stress tolerance by networking with DRE/CRT cis-regulatory elements in response to stresses. In this study, bioinformatics analysis was performed to conduct the genome-wide identification and characterization of DREB genes and promoter elements in Solanum lycopersicum. In genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…With reference to literatures describing CRE [ [18] , [19] , [20] ], the phytohormone-, stress-, and development-related CREs in 18 flavonoid biosynthetic pathway genes promoter regions were identified in S. suberectus and visualized by heatmap ( Fig. 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…With reference to literatures describing CRE [ [18] , [19] , [20] ], the phytohormone-, stress-, and development-related CREs in 18 flavonoid biosynthetic pathway genes promoter regions were identified in S. suberectus and visualized by heatmap ( Fig. 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several hormone-responsive cis-elements were also present in the promoters of VvBTB genes. For example, the As-I element involved in auxin and methyl jasmonate (MeJA) signaling was present in the promoters of several VvBTB genes [64]. Methyl jasmonate (MeJA) plays a crucial role in plant biotic stress resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we compared the expression levels of six drought-responsive marker genes: SlDREB1 (Solyc06g050520), SlDREB2 (Solyc12g008350), SlDREB3 (Solyc04g072900), SlGRAS4 (Solyc01g100200), SlNCED (Solyc07g056570), and SlGA2OX7 (Solyc02g080120), which were previously reported to positively respond to drought stress [51][52][53][54]. Our results showed that these genes were upregulated by dehydration treatment, suggesting the identification of overlapping regulators of drought and dehydration response by transcriptomic profiling in this study (Figure S4).…”
Section: Differentially Expressed Tfsmentioning
confidence: 99%